1971
DOI: 10.1107/s056774087100205x
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction study of sodium thiosulphate pentahydrate, Na2S2O3.5H2O

Abstract: A single-crystal neutron-diffraction investigation of sodium thiosulphate pentahydrate, Na2S203.5H20, has been made with three sets of zonal data. The structure was refined by least-squares techniques, with individual temperature factors, to an R value of 8.2%. The geometry of the $203 group and sodium-oxygen framework agree with those of X-ray studies. The positional parameters of some of the atoms differ from those p3stulated from the X-ray and nuclear magnetic resonance studies. The O-H and H-H bond distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
5
5
0
Order By: Relevance
“…E1 Saffar (1968) has reported the positional parameters of H atoms deduced from his NMR studies. Padmanabhan et al (1971) refined the abovementioned crystal structure from two-dimensional neutron diffraction data and they basically confirmed the hydrogen-bonding scheme as proposed by Taylor &Beevers (1952) andEl Saffar (1968), with the exception of atom H(9). Baur (1972) suggests that this disagreement needs clarification.…”
Section: Introduction Experimentalsupporting
confidence: 78%
See 2 more Smart Citations
“…E1 Saffar (1968) has reported the positional parameters of H atoms deduced from his NMR studies. Padmanabhan et al (1971) refined the abovementioned crystal structure from two-dimensional neutron diffraction data and they basically confirmed the hydrogen-bonding scheme as proposed by Taylor &Beevers (1952) andEl Saffar (1968), with the exception of atom H(9). Baur (1972) suggests that this disagreement needs clarification.…”
Section: Introduction Experimentalsupporting
confidence: 78%
“…to 0.13. At this stage, unlike Padmanabhan et al (1971), we found evidence of extinction and the 25 severely extinctionaffected reflexions were corrected for extinction effects (Aydin Uraz & Arma~an, 1975) as described by Zachariasen (1967) and Killean, Lawrence & Sharma (1972). With these extinction-corrected structure amplitudes in two cycles of isotropic refinement, R and R, reduced to 0.10 and 0.11 respectively.…”
Section: (3)supporting
confidence: 58%
See 1 more Smart Citation
“…The geometry and bonding in the SzO]-ion (Table 6) are similar to those observed in two other ionic thiosulphates, MgSzO3.6H20 (Baggio, Amzel & Becka, 1969) and NazSzO3.5H20 (Padmanabhan et al, 1971). Thus the bond angles subtended at the central sulphur atom, which range from 108.1 (2) ° to 110.9 (2) °, reveal only slight distortions from ideal tetrahedral symmetry, and the bond lengths indicate considerable zc bonding character in both S-O and S-S bonds.…”
Section: The Environment Of the Barium Ionsupporting
confidence: 71%
“…Typically, hydrogen bonding networks involving all water molecules in O-H···O and O-H···S bonds with S 2 O 3 2− anions are observed [7]. So far several crystal structures of alkali metal thiosulfate hydrates are well characterized and the hydrogen bonding systems therein have been discussed: K 2 [13][14][15][16]. A detailed classification of the hydrogen bonds is available for Na 2 S 2 O 3 ·5H 2 O.…”
Section: Introductionmentioning
confidence: 99%